Siyāsah syar’iyyah and Its Application to Constitutional Issues in Indonesia - Maimun, Maimun; Hakim, Dani Amran (As-Siyasi: Journal of Constitutional Law, 2023)
Siyāsah Syar’iyyah  (Islamic legal politics) is a political doctrine in Islam based on revealed values (Sharia), which in practice constructs state laws to regulate, control, manage, and administer the governance and politics of an Islamic state. It aims to achieve welfare and avoid harm without violating Sharia's universal principles and provisions. This study examines Siyāsah Syar’iyyah  (Islamic legal politics) towards constitutional issues in Indonesia. The method used is a literature study with a conceptual approach. Based on its nature, this research is descriptive, and the research data used is secondary. The study results show that Siyāsah Syar’iyyah is a type of siyāsah (legal policy) constructed by the ruler (ulil amri).  The formation of laws is based on religious moral values, which are applied to regulate life in society, nation, and state. Siyāsah Syar’iyyah  (Islamic legal politics) can be a part of implementing constitutional issues in Indonesia. For Indonesian Muslims in this contemporary era, Siyāsah Syar’iyyah has become necessary primarily in the political year (2023-2024) as a barometer to assess whether these issues are categorized as Islamic (‘ādilah) or not (ẓālimah).